Existentialists or mystics. Kierkegaard and Murdoch on imagination and fantasy in ethical life. Issue 3 (3rd April 2021) - Compaijen, Rob
ABSTRACT: In this paper I explore the role of imagination in ethical life. I do so by discussing the thought of Kierkegaard and Murdoch, both of whom stress the importance as well as the dangerousness of imagination for ethical life. Both distinguish between proper imagination and mere fantasy in dealing with the tension. Anti-Climacus's views on imagination emphasize that the proper use of the imagination plays a vital role in realizing the fundamental ethical task of becoming ourselves, whereas fantasy only alienates us from ourselves. Murdoch's account of imagination stresses that a proper use of the imagination contributes to the realization of a selfless attunement to the world, whereas fantasy only reinforces the (what she describes as) 'fat, relentless ego'. In the final part of the paper I discuss some existing comparisons between both accounts. I conclude by drawing attention to the fundamental choice that comparing their views on the role of imagination in ethical life confronts us with: should we be existentialists or mystics in ethics?